2017
DOI: 10.1002/lsm.22736
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β‐catenin and ERK pathway activation: A possible mechanism of photobiomodulation therapy with light‐emitting diodes that regulate the proliferation of human outer root sheath cells

Abstract: These results demonstrate that LED light irradiation induced hORSC proliferation and migration and inhibited apoptosis in vitro. The growth-promoting effects of LEDs on hORSCs appear to be associated with direct stimulation of the Wnt5a/β-catenin and ERK signaling pathway. Lasers Surg. Med. 49:940-947, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Interestingly, several authors have reported the effects of PBM on signalling molecules involved in this pathway. In their study, Kim et al evaluated the response of human outer root sheath cells to PBM at wavelengths of 415 nm, 525 nm, 660 nm or 830 nm (142). Notably they found that PBM induced an increase in ERK phosphorylation.…”
Section: Extracellular-regulated Kinase (Erk) Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, several authors have reported the effects of PBM on signalling molecules involved in this pathway. In their study, Kim et al evaluated the response of human outer root sheath cells to PBM at wavelengths of 415 nm, 525 nm, 660 nm or 830 nm (142). Notably they found that PBM induced an increase in ERK phosphorylation.…”
Section: Extracellular-regulated Kinase (Erk) Signallingmentioning
confidence: 99%
“…Several authors have reported the effects of PBM on p38 MAPK signalling. Interestingly, both Kim et al and Chu et al concluded that red light PBM induced increased p38 phosphorylation and therefore increases in the activity of this pathway (142,144). However, a further study concluded that following application of red light, there was a decrease in p38 phosphorylation (145).…”
Section: P38 Mapksmentioning
confidence: 99%
“…Low Level Laser Light Therapy (LLLT) is widely used as alternative medical treatment in wound healing and to relieve pain and inflammation. The effects of light therapy on hair growth have been investigated via DPCs . In addition, electromagnetic field resulted in stimulation of DPCs activity .…”
Section: Hair Growth Promoting Effectmentioning
confidence: 99%
“…Recent studies pointed out that INH could induce HepG2 cell injury by repressing SIRT1 expression . Extracellular signal‐regulated kinase (ERK) regulates various cellular processes, like cell proliferation, cell differentiation, and cell cycle progression in response to various extracellular signals . INH is believed to induce apoptosis by inhibiting ERK phosphorylation .…”
Section: Introductionmentioning
confidence: 99%